Japan’s New Trade Policy – A Policy Transformation Without Strategy? - Jamitzky, Ulli (2017)
Japan’s trade policy has undergone major changes in recent years. This policy shift manifests itself in Japan’s turn towards bilateral and plurilateral trade agreements as a new pillar of its trade policy. In this book, the author identifies and analyzes the main driving forces and actors behind this policy change and discusses its potential political and economic ramifications. This book also raises the question on why Japan has failed to conduct a comprehensive and transparent evaluation of its new trade policy. The author draws on 25 expert interviews with policy makers, bureaucrats and other experts on Japanese trade policy to unveil deep insights into the complex process of trade policy-making in Japan.Permalink https://nbn-resolving.de/urn:nbn:de:hbz:6-02239638052ISBN978-3-8405-0156-2Paperback, V, 204 Seiten